Paedophilia in modern society a mirror of pederasty of Ancient Greece? (2021)
As never before, sexual abuse is rife in modern human society. Tracing the beginnings of sexual perversions to ancient Greece where pederasty was institutionalised, this paper attempts a conceptual distillation between paedophilia and pederasty. Given that pederasty in ancient Greece was an institutionalised part of aristocracy, existing between an adult male, erastes, and a pre-adolescent boy, the eromenos, some scholars have argued that paedophilia is an offshoot of this Greek practice. These scholars make references to canonical philosophical writings by Plato, Xenophon, and Aristophanes inter alia as authority to prop their arguments for indulging the modern phenomena of paedophilia as well as homosexuality by extension. The arguments presented, in this study, bifurcates pederasty from paedophilia by drawing copiously from the sociological and psychological perspectives in deconstructing those widely held views on both sexual Orientations. The study reveals that the former is a norm that left a multiplier effect as the pederast mentee developed to the extent of becoming a pederast mentor, thereby promoting sustainable development in ancient Greece. The study concludes that both concepts exist on different orientational pedestals with pederasty to be lauded for its gains and paedophilia to be condemned for its evils against the innocent child victim